Fuzzy Tuning and Power Reaching Law-Based Discrete Sliding Mode Control for Solar Photovoltaic Inverters. (April 2019) - Chang, En-Chih; Cheng, Hung-Liang; Cheng, Chun-An
Abstract: This paper develops a digital signal processor (DSP)-controlled solar photovoltaic inverter that is well realized to prove the proposed controller. The discrete sliding mode control (DSMC) with power reaching law (PRL) not only suits for digital implementation because of its finite sampling frequency but permits faster convergence speed. However, the chattering around PRL-based DSMC exists and may cause excessive power losses. A fuzzy tuning technology is employed to handle the problem of the chattering so that the robustness of the system can be increased. Simulation results display that the proposed solar photovoltaic inverter can generate low total harmonic distortion (THD) under rectifier-type load circumstances and fast transient response under step load changes. Experimental results on a solar photovoltaic inverter laboratory prototype controlled by a digital controller are provided to substantiate both theoretical analysis and simulation results.